Advanced 3D printed bone scaffolds with sodium alginate/Tri-calcium phosphate/probiotic bacterial hydroxyapatite: Enhanced mechanical and biocompatible properties for bone tissue engineering - ULAĞ, SONGÜL; GÜNDÜZ, OĞUZHAN; ÇALIKOĞLU KOYUNCU, AYŞE CEREN (My University, 2024)
Introduction: The increasing prevalence of severe bone diseases, such as osteoporosis and critical bone defects, necessitates the development of more effective bone substitutes. This study addresses this need by investigating 3D-printed bone scaffolds composed of sodium alginate and tricalcium phosphate, enhanced with three distinct types of hydroxyapatite (HA): bovine-derived HA, commercially available HA, and HA enriched with probiotic bacteria. We aim to evaluate the performance of these scaffolds in terms of mechanical strength, biocompatibility, and their ability to support bone regeneration. Methods: The scaffolds were analyzed through various tests, including X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) to characterization. Scanning Electron Microscopy (SEM) was used to examine pore structure, while swelling and degradation tests evaluated the scaffold\"s stability. Compression testing determined mechanical strength, and in vitro cell culture assays assessed cell proliferation, osteogenic differentiation, and biomineralization. Results: SEM results indicated that 3D scaffolds with probiotic bacterial HA had the desired 472 μm pore size. These scaffolds demonstrated a strain of 29.26 % and a compressive strength of 10 MPa, meeting the mechanical standards of human trabecular bone. Cell culture studies revealed enhanced cell proliferation by 50 %, osteogenic differentiation with 15.3 U/mg ALP activity, and 1.22-fold biomineralization, suggesting they are highly biocompatible and promote bone growth. Conclusion: Probiotic bacterial HA scaffolds exhibit ideal properties and biocompatibility, enhancing bone regeneration and serving as an ideal alternative to chemical types.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik Bilişim Ve Teknoloji (Eng); Temel Bilimler (Sci); Malzeme Bilimi; Malzeme Bilimi Çokdisiplinli; Polimer Bilimi; Kimya Organik; Engineering Computing & Technology (Eng); Natural Sciences (Sci); Materials Science; Materials Science Multidisciplinary; Polymer Science; Chemistry Organic; Organik Kimya; Fizik Bilimleri; Polimerler ve Plastikler; Malzeme Kimyası; Organic Chemistry; Physical Sciences; Polymers and Plastics; Materials Chemistry; 3D printing; Biocompatibility; Bone scaffold; Probiotic bacterial hydroxyapatite